SEGS-1 episomes generated during cassava mosaic disease enhance disease severity - Chiunga, Evangelista; Aimone, Catherine D.; Rajabu, Cyprian; Dallas, Mary M.; Ndunguru, Joseph; Ascencio-Ibáñez, José T.; Ateka, Elijah M.; Hanley-Bowdoin, Linda (Frontiers in Plant Science, 2025)
Cassava is an important root crop that is produced by smallholder farmers across Sub-Saharan Africa. Cassava mosaic disease (CMD), which is caused by a group of cassava mosaic begomoviruses (CMBs), is one of the most devastating diseases of cassava. A previous study showed that SEGS-1 (sequences enhancing geminivirus symptoms), which occur both in the cassava genome and as episomes during CMD, can increase CMD disease severity and overcome host resistance. In this report, we examined the effects of exogenously applied SEGS-1 on the incidence of CMB infection, symptom severity, and viral DNA copy number in five cassava cultivars that ranged from highly susceptible to highly resistant to CMD. These studies revealed that the effect of SEGS-1 is cultivar dependent. Susceptible cultivars developed severe CMD with or without exogenous SEGS-1, while exogenous SEGS-1 increased disease severity in cultivars carrying CMD2 resistance, which is conferred by a single locus, but not CMD1 resistance, which is polygenic. Analysis of infected plants in the absence of exogenous SEGS-1 revealed that some, but not all, cultivars form SEGS-1 episomes during CMD. The presence of endogenous SEGS-1 episomes in TME14, a CMD2 resistant cultivar, correlated with CMD severity. In contrast, TME3, a closely related CMD2 cultivar, did not produce endogenous SEGS-1 episomes and was more resistance than TME14. The different capacities of TME3 and TME14 to form SEGS-1 episomes is unlikely due to sequence differences in and around their genomic SEGS-1 loci. The functional regions of SEGS-1 were mapped using TME3 to sequences flanking the episome junction, but the junction itself was not required for activity. All cassava cultivars have SEGS-1 sequences in their genomes that have the potential to negatively impact the development of stable CMD resistance by cassava breeding programs.